2018
DOI: 10.1158/1055-9965.epi-17-0995
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Disease-Free Survival by Breast Density and Phenotype in Interval Breast Cancers

Abstract: We aimed to evaluate survival and disease-free survival in different subtypes of interval cancers by breast density, taking into account clinical and biological characteristics. We included 374 invasive breast tumors (195 screen-detected cancers; 179 interval cancers, classified into true interval, false-negatives, occult tumors and minimal-sign cancers) diagnosed in women ages 50-69 years undergoing biennial screening from 2000-2009, followed up to 2014. Breast density was categorized into non-dense (<25% den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
2
9
1
Order By: Relevance
“…We used Cox regression with time since diagnosis as the time variable to estimate hazard ratios (HRs) with 95% CIs for the risk of death from all causes in true, minimal signs, and missed cancers. We adjusted for age at diagnosis and included tumour diameter, grade, and subtype as confounders based on a priori knowledge of their relationship with the exposure and outcome in interval cancers [17][18][19][20][21][22]. All analyses were conducted separately for screen-detected and interval cancers due to the potential for lead time bias in combined analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used Cox regression with time since diagnosis as the time variable to estimate hazard ratios (HRs) with 95% CIs for the risk of death from all causes in true, minimal signs, and missed cancers. We adjusted for age at diagnosis and included tumour diameter, grade, and subtype as confounders based on a priori knowledge of their relationship with the exposure and outcome in interval cancers [17][18][19][20][21][22]. All analyses were conducted separately for screen-detected and interval cancers due to the potential for lead time bias in combined analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that true interval cancers are more likely to be smaller [17,18,[20][21][22] and histologic grade 3 [17-19, 21, 22] than missed interval cancers. Our results confirmed that true interval cancers are more likely to be grade 3, but found no more than a 1 mm difference in the median histopathologic tumour diameter of true, minimal signs, and missed cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hospitals involved were all in Spain––in the Costa del Sol (Marbella), the Canary Islands, Sabadell, and Gerona––and the diagnoses and surgical interventions all took place during the period 2000‐2008, with follow‐up to 2014. The women in the study population were mainly derived from the retrospective cohort of the CAMISS study (n = 1086) and the rest had been diagnosed within the screening program provided at the Costa del Sol Hospital, Marbella …”
Section: Methodsmentioning
confidence: 99%
“…The women in the study population were mainly derived from the retrospective cohort of the CAMISS study (n = 1086) and the rest had been diagnosed within the screening program provided at the Costa del Sol Hospital, Marbella. 12 The following inclusion criteria were applied:…”
Section: Study Populationmentioning
confidence: 99%